Perubahan Fungsi dan Makna Peribahasa dalam Laman Facebook (Changes of the Function and Meaning of the Malay Proverbs in Facebook) - Jaafar, Salinah; Sani, Huraizah Abd; Haron, Rohaidah (Universiti Kebangsaan Malaysia Press, 2018)
Proverbs has been existed in the Malay society since long time ago. Proverbs being delivered indirectly and smoothly to symbolize and impart certain meanings implicitly. The proverb was created by the existence of the nation and was presented in old Malay literature that was not recorded in writing. Proverbs are delivered through the lips or verbal from mouth to mouth. Proverbs that have been produced symbolizes the minds of the Malay community were always trying to shape and educate children through memorable words and as rules, guides and advice in everyday life. Nowadays proverbs have been spread widely compared to the old time. The emergence of today's growing technology in tandem with the advancement of the wireless world has succeeded in linking communities around the world. Social media is one of the internet technologies that have been succeeded in establishing and connecting people immediately around the world. The use of social media is increasing day by day regardless of age and consumer groups. Social media often gets attention in delivering express information quickly without being filtered or blocked by any party. This quick and effective delivery makes it a necessity in today's society. Due to that, this article will discuss the changing of function and meaning of the proverb with the focus of the study on the data taken from the media social Facebook.